Analisis Defect Proses Produksi Songkok Berbasis Metode FMEA Dan FTA di Home - Industri Songkok GSA Lamongan - Ayu Lestari; Nina Aini Mahbubah (Fakultas Teknik, 2021)
Small and Medium sized enterprises are recognized as national safety net during crisis era in this nation. Gangsar is a small-sized enterprise and recognized as songkok home industry in Lamongan City. Maintaining sustainable quality is known as both challenge and weakness in order to sustain its business. The research purpose is to identify defect and analyze it in order to improve product quality. Failure Mode and Effect Analysis and Fault Tree Analysis were used as research method. This research begun with mapping flow production process in order to identified defect product. Once defect product was recognized, the next stage was calculating risk priority number. Mapping fault tree was the next stage to detect failure mode. The results showed three defects identified namely trimmed with Risk Priority Number144, disorderly sewing process with RPN 126 and non-precision cutting fabric with RPN 86. These defects have been analyzed using FTA and it was found factors such as human errors, no-good material, and broken sewing machines need to be eliminated. Improving work facilities and regular training as well as working supervision are considered as better scenario in order to sustaining product quality.